ANALISA PERAWATAN MESIN EVAPORASI MINYAK KELAPA MURNI UD ZUBERDIN SAGINI DESA JEREWEH SUMBAWA BARAT DENGAN MENGGUNAKAN METODE PREVENTIVE MAINTENANCE - Eko Wijaya; Ismi Mashabai; Ahyar Andika; Nurmila Nurmila (Fakultas Teknik Universitas Tulang Bawang Lampung, 2022)
The development of the industrial world today develops very rapidly over time, and so are the existing technological advances. Micro, Small and Medium Enterprises (MSMEs) are economic business activities owned by individuals or groups in accordance with the criteria set by Law number 20 of 2008. In this case, of course, MSME actors have superior products produced in them One of the SMEs in West Sumbawa by producing products, namely UD Zuberdin. The number of types of products produced certainly requires a high level of quality. One of the factors that can support quality is the quality of the machine. The machine is the main thing that needs to be considered in the production process, therefore it is necessary in a company to carry out the maintenance and maintenance of the machine. One of the systems in machine maintenance and maintenance is preventive maintenance. Preventive maintenance is a maintenance that is carried out on a scheduled basis generally periodically (Ebeling., 1997).